An Analysis of Gratitude Role as The Religiosity Form Towards Subjective Well-Being in College Students - Hayuningtyas, Krisbandaru; Jenuri, Jenuri (Journal of Islamic and Contemporary Psychology, 2023)
Every individual ran through a transitional period of self-development and also a school where the higher the level of education, the higher of demands that must be faced. The developmental age of students was the most productive age as well as being the age stage that was vulnerable to experiencing stress, physical fatigue, and mental fatigue. It can affect individual psychological well-being or often known as subjective well-being. One of the things that influence subjective well-being was gratitude. Gratitude was a form of religiosity that can increase positive emotions and affect thus it can affect good subjective well-being. Good subjective well-being will lead a person to life satisfaction, happiness, and success in his life. The method used the library study, the aim of research was to find out the description of the role of gratitude as a form of religiosity towards subjective well-being in college students.